The twelve chairs [videorecording (DVD)] - Brooks, Mel, 1926-; Moody, Ron; Langella, Frank; DeLuise, Dom; Ilʹf, Ilʹi͡a, 1897-1937 (20th Century Fox Home Entertainment, 2006)
When a former aristocrat who is now a Russian clerk under the new Soviet regime learns that his dying mother-in-law sewed a fortune of family jewels into one of twelve dining room chairs, he sets off across Russia to find it--with an opportunist, a priest and his former servant all in pursuit.